Theatre pedagogy as an area of negotiating and understanding complex concepts by kindergartners in times of crisis: an intervention-based research study - Giotaki, Marianna; Lenakakis, Antonis (Preschool and Primary Education, 2016)
In this research theatre pedagogy was used to explore kindergartners’ perceptions of the economic crisis and its aspects in their everyday lives, as well as to provide them with opportunities to invest crisis situations with a positive, dynamic meaning, and to shift towards the humanitarian values of justice, active citizenship and understanding the other. Through our theatre-pedagogic programme, a social topic was put forward to the class, and performing arts tools were used to generate a framework for seeking solutions and finding meaning. Research results corroborate the value of theatre pedagogy to kindergartners negotiating, expressing and understanding complex concepts like those of the economic crisis and its aspects. Theatre pedagogy can also generate empathy in kindergartners for what is unusual, different, or seemingly distant and irrelevant.